Mechanism of action of quercetin in regulating cellular autophagy in multiple organs of Goto-Kakizaki rats through the PI3K/Akt/mTOR pathway - Guo, Zhiqun; Zhang, Jingyu; Li, Mianxin; Xing, Zengwei; Li, Xi; Qing, Jiaqi; Zhang, Yuan; Zhu, Lemei; Qi, Mingxu; Zou, Xuemin (Frontiers in Medicine, 2024)
Objective This experimental study investigated the protective function of quercetin on the liver, spleen, and kidneys of Goto-Kakizaki (GK) rats and explores its mechanism of action on autophagy-related factors and pathways. Materials and methods GK rats were randomly divided into three groups: DM, DM + L-Que, and DM + H-Que, with age-matched Wistar rats serving as the control group. The control and DM groups were gavaged with saline, and the quercetin-treated group was gavaged with quercetin for 8 weeks each. Weekly blood glucose levels were monitored. Upon conclusion of the experiment, blood samples were gathered for lipid and hepatic and renal function analyses. The histopathologic morphology and lipid deposition in rats were examined. Disease-related targets were identified using molecular docking methods and network pharmacology analysis. Subsequently, immunohistochemical analysis was performed, followed by Western blotting to evaluate the levels of autophagy-related proteins and proteins in the AKT/PI3K/mTOR pathway, as well as their phosphorylation levels. Results The results showed that, compared with the control group, the DM group exhibited significant increases in blood glucose, serum liver and kidney markers, liver fat vacuoles, and inflammatory cell infiltration. Immunohistochemistry (IHC) results indicated that quercetin reduced the extensive expression of AKT, P62, and mTOR in the liver and spleen of diabetic rats. The expression of autophagy and pathway-related proteins, such as P62, PI3K, P-PI3K, Akt, P-AKT, mTOR, and P-mTOR, was upregulated, while the expression of LC3A/LC3B, Beclin-1, Pink-1, and Parkin was downregulated. Conversely, the quercetin group showed a reduction in liver and kidney injury serum markers by decreasing lipid deposition and cell necrosis, indicating that quercetin has protective effects on the liver, spleen, and kidneys of GK rats. Additionally, in the quercetin group, the expression of autophagy and pathway-related proteins such as LC3A/LC3B, Beclin-1, Pink-1, and Parkin was upregulated, while the expression of P62, PI3K, P-PI3K, Akt, P-AKT, mTOR, and P-mTOR was downregulated, with statistically significant correlations. Conclusion Quercetin markedly ameliorates liver, spleen, and kidney damage in GK rats, potentially through the inhibition of the PI3K/Akt/mTOR pathway, promoting autophagy. This research offers a rationale to the therapeutic potential of quercetin in mitigating organ damage associated with diabetes.